The Historiography of the Pedagogical System of Friedrich Froebel - Mashkina, Lyudmyla (Pedagogical Discourse, 2013)
The article analyzes some historiographical acquisitions regarding the educational system of Friedrich Froebel, its major focus. The scientific sources are highlighted in the context of the main aspects of Froebel’s ideas of the theory and practice of pre-school education. The works of outstanding personalities of pre-school education are characterized, which disclose the contents of Froebel’s system, leading ideas of his kindergarden, play, formation of pedagogical process on gaming principles, mechanisms of children’s intellectual development. In particular, these are works of S.F.Rusova, K.D.Ushinskyi, O.P.Usova etc. The works of A.Paramonova, D.Nikolenko, Z.Borysova are also highlighted. They describe Froebel’s gifts, games, activities, processes of children’s socialization, taking into account their personalities and humanistic attitude to them.